Development of technologies of electronic banking in Ukraine - Kapinus, Larisa; Skryhun, Natalya (My University, 2014)
Understanding of the state of electronic banking in Ukraine requires forming of concept-category apparatus and information updating for the problems exposure and prospects of electronic bank services development.The aim of the article is improvement of category apparatus that is related to the concept of «electronic banking», and modern progress exposure of the Internet banking trends in Ukraine.
Keywords: e-banking; Internet-service; electronic services market; електронний банкінг; інтернет-послуга; ринок електронних послуг; электронный банкинг; рынок электронных услуг; кафедра маркетингу